Expectations of train drivers for innovative driving cabin. Issue 29 (2022) - Merlevede, Jean-Valentin; Enjalbert, Simon; Henon, Frédéric; Baños, Alexandre Pereda; Ricci, Stefano; Vanderhaegen, Frédéric
Abstract: This paper aims at identifying the expectations of train drivers or other railway staff about Human-Machine Systems (HMS) in future cabins. The identification of the best technical solution needs surveying preferences and efficiencies of possible new information technology configurations of Human-Machine Interfaces (HMI) considering human factors as input and output sensors. Technical recommendations about the train cabin of the future are provided. They consider results from a state-of-the-art on HMI in transport systems, from technology maturity issues, and from two large scale surveys realized during project. Recommendations are then proposed to train manufacturers for deeper investigation or for innovative driving cabin implementation.